Construction and validation of Social Work intervention complexity scale in hospital care settings - Carvalho, H.; Espirito Santo, M.; Ferreira, J. (British Journal of Social Work, 2022)
The aim of this article was to develop and validate a scale to measure the complexity of social intervention with adults in hospital care settings. Two separate studies were conducted (N1 = 224 and N2 = 224). Study 1 was focused on the development of the Social Work Intervention Complexity (SWIC) scale and on its dimensionality. The exploratory factorial analysis was conducted to identify its factor structure, and reliability was assessed. Study 2 examined the construct validity of the scale and tested its robustness in the two samples with an invariance test. Single-group and multi-group confirmatory factor analyses were used. The results confirmed a three-factor structure and convergent validity, and discriminant validity was guaranteed. The invariance of the measuring instrument across the two groups was also proved. The practical implications arising from the validation of the SWIC scale are also a distinctive feature of this work. The application can be implemented to monitor the complexity of social intervention with adults in hospital care settings. In the future, different hospitals could integrate the application of the SWIC scale into their protocol since the social worker's professional practice must be combined with scientific rigor and the quality of social intervention.